2022
DOI: 10.1037/vio0000391
|View full text |Cite
|
Sign up to set email alerts
|

The role of five-factor model traits in predicting physical and verbal aggression during the transition to college.

Abstract: Objective: The present study aimed to investigate the developmental trajectory of adolescents' aggression and the role of the Five-Factor Model (FFM) traits during the transition to college. Method: A sample of 973 Chinese college freshmen (73.9% females) was recruited to complete the Neuroticism-Extraversion-Openness (NEO) Five-Factor Inventory and Aggression Questionnaire with a short-term longitudinal research design across four waves with an interval of 1 month between waves. We calculated bivariate relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For instance, people with higher levels of neuroticism are more likely to experience painful and irrational thoughts. They may then engage in aggressive behaviors [11,13]. On the other hand, people with higher levels of agreeableness are less likely to engage in aggressive behaviors [14].…”
Section: Big Five Personality Traits and Aggressionmentioning
confidence: 99%
“…For instance, people with higher levels of neuroticism are more likely to experience painful and irrational thoughts. They may then engage in aggressive behaviors [11,13]. On the other hand, people with higher levels of agreeableness are less likely to engage in aggressive behaviors [14].…”
Section: Big Five Personality Traits and Aggressionmentioning
confidence: 99%
“…These limitations and a need for future research notwithstanding, the current findings offer initial support for the severity-matching strategy and using a normal-range personality trait measure when assessing violence risk in college settings. Use of normal-range personality trait measures is further supported by other investigations showing normal-range personality traits’ associations with verbal and physical aggression in college students (e.g., T. Hu et al, 2022).…”
Section: Discussionmentioning
confidence: 60%
“…These limitations and a need for future research notwithstanding, the current findings offer initial support for the severity-matching strategy and using a normal-range personality trait measure when assessing violence risk in college settings. Use of normal-range personality trait measures is further supported by other investigations showing normal-range personality traits' associations with verbal and physical aggression in college students (e.g., T. Hu et al, 2022). Preliminary support for the severity-matching strategy is strengthened by its grounding in IRT where models of testing, such as computer adaptive testing, demonstrate the important relationship between trait levels, item difficulty, and item response (DeMars, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…In the college stage, the forms of aggression are more diverse, such as physical aggression, relationship aggression, cyber aggression, and intimate partner aggression (Marganski & Melander, 2018; Thomas, 2019). In addition, several studies have revealed that aggressive behavior increases during the first year of college (Hu et al, 2022; Swartout et al, 2015). Hu et al (2022) found that physical aggression showed an increased linear trajectory across the first 4 months of college.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have revealed that aggressive behavior increases during the first year of college (Hu et al, 2022; Swartout et al, 2015). Hu et al (2022) found that physical aggression showed an increased linear trajectory across the first 4 months of college. Swartout et al (2015) also found that sexually aggressive behavior was highest in the first year of college and decreased in subsequent years.…”
Section: Introductionmentioning
confidence: 99%